The Effectiveness of ‘Cermati’ Media (Intelligent Measuring Anthropometry) to Increase Knowledge and Skills of Cadres in Stunting Screening - Murti Ani; Novita Ika Wardani; Dina Dewi Anggraini (JURNAL KEBIDANAN, 2024)
Stunting is still a problem in Indonesia. In 2022, the stunting rate will still be high, namely 21.6%, with the expected national target in 2024 being 14%. The lack of understanding and skills of cadres in anthropometric measurements causes many of the results of weighing, data collection and recording of stunting detection to be inaccurate. The purpose of this study was to determine the effect of ‘cermati’ media (intelligent measuring anthropometry) to increase knowledge and skills of cadres in stunting screening. The research design was a quasi-experimental design with a pre-posttest with control group design conducted in Blora Regency from June to August 2023. The instrument used is a questionnaire. The population in this study were all cadres in Blora Regency. The sample in this study were 26 experimental respondents and 26 control respondents. Data analysis used the independent t-test. The results showed that there was an effect of the ‘cermati’ media (intelligent measuring anthropometry) to increase knowledge (p-value 0.000) and skills of cadres in stunting screening (p-value 0.000). Thus, the ‘cermati’ media (intelligent measuring anthropometry) can be used as an effort to increase knowledge and skills of cadres in stunting screening.